Effect of Voltage Variation on the Properties of Gas Tungsten Arc Welded Low Carbon Steel - Oluigbo, Chiedozie Valentine; Mgbemere, Henry Ekene (Kathmandu University Journal of Science, Engineering and Technology, 2023)
This research was necessary as only limited work had been carried out on the effects of arc voltage on the mechanical properties of welded low- carbon steel using Gas Tungsten Arc Welding (GTAW). Even though it is pretty expensive compared to other welding types due to the required shielding gas, GTAW processes have the advantage of being automated with continuous feeding of the electrode into the weld and avoiding the production of fused flux or slag layer. It becomes imperative to determine the effect of welding parameters on the microstructure and mechanical properties of welded joints using GTAW at a fixed current (115A) but with varying voltage. The low carbon steel specimen employed has a thickness of 5 mm, while the electrode used was the E6013 electrode with a tungsten size of 2.4 mm and a filler rod size of 3.2 mm. The effects of voltage variations at different levels, specifically 200V, 205V, 210V, 215V, 220V, and 225V, on the microstructure and mechanical properties of GTAW weldments were investigated. Adjusting voltage levels while maintaining a constant current of 115A increased hardness values and decreased tensile strength and impact toughness compared to the unwelded sample. The increase in hardness of the welded steel can be attributed to the formation of a fine grain structure and intermetallic phase, as observed in the micrographs. Also, the ultimate tensile strength, ductility, and Young’s modulus decrease as the voltage increases from 200V to 210V, followed by an increase as the voltage rises from 215V to 225V compared to the unwelded sample. The observed variances in the properties of the material were attributed to the high concentrations of sulfur (0.07%), manganese (1.48%), and phosphorus (0.22%) present in both the base metal and electrode utilized.